2000
DOI: 10.3758/bf03206917
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual anticipation in handwriting: The role of implicit motor competence

Abstract: In two experiments, perceptual anticipation-that is, the observer's ability to predict the course of dynamic visual events-in the case of handwriting traces was investigated. Observers were shown the dynamic display of the middle letter I excerpted from two cursive trigrams (lU or Un) handwritten by one individual. The experimental factor was the distribution of the velocity along the trace, which was controlled by a single parameter, {3. Only for one value of this parameter ({3 =2/3) did the display comply wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(55 citation statements)
references
References 33 publications
3
49
0
3
Order By: Relevance
“…Sebanz & Shiffrar, 2009). Typical adults are better at predicting movement outcomes that comply with typical kinematic trajectories (Kandel, Orliaguet, & Viviani, 2000), and those with more experience of performing a particular action are better able to predict the outcome of that action when it is observed (Diersch et al, 2012). The present study adds to these findings by showing that we are better at making higher-level mental state inferences (e.g., coaxing) from actions that look like our own 2 .…”
Section: Discussionsupporting
confidence: 55%
“…Sebanz & Shiffrar, 2009). Typical adults are better at predicting movement outcomes that comply with typical kinematic trajectories (Kandel, Orliaguet, & Viviani, 2000), and those with more experience of performing a particular action are better able to predict the outcome of that action when it is observed (Diersch et al, 2012). The present study adds to these findings by showing that we are better at making higher-level mental state inferences (e.g., coaxing) from actions that look like our own 2 .…”
Section: Discussionsupporting
confidence: 55%
“…If an actor pretends, say, that a suitcase he is carrying is heavier than it actually is, his movements will have a non-natural kinematics that can be detected by observers. Another series of experiments (Orliaguet et al, 1997;Kandel et al, 2000) investigated motor anticipation in the perception of handwriting gestures. For instance, when writing an l, the kinematics of the graphic production is influenced by anticipation of the next letter to be written and will differ according to whether the l is to be followed by another l, an i or a n. It was shown that the visual system can exploit these differences to predict the second letter.…”
Section: Imagining and Observing Actions: Simulation And The Limits Omentioning
confidence: 99%
“…In a related study, Kandel, Orliaguet, and Viviani (2000) showed participants excerpts of three-letter sequences being handwritten in cursive. Only the middle letter was shown, and the participants' task was to guess which of two letters would be the third letter, based on the movement they perceived in the writing of the middle letter.…”
Section: Interpreting Point-light Displays and Apparent Motion Displaysmentioning
confidence: 99%